Life after life : a novel - Atkinson, Kate. (New York : Reagan Arthur Books/Little, Brown and Company, 2013)
In 1910, Ursula Todd is born to an English banker and his wife. She dies before she can draw her first breath. On that same cold and snowy night, Ursula Todd is born, and embarks upon a life that will be, to say the least, unusual. For as she grows, she also dies, repeatedly, in a variety of ways, while the young century marches on towards its second cataclysmic world war.
Keywords: Reincarnation -- Fiction; Great Britain -- History -- 20th century -- Fiction; Alternative histories (Fiction); Humorous fiction